2021
DOI: 10.7759/cureus.20113
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Cholecystectomy and Colorectal Cancer in the Female Gender

Abstract: Colorectal carcinoma (CRC) has been of great interest among researchers, and multiple causes have been proposed and accepted; however, cholecystectomy (CMY) as a potential cause for CRC, particularly in the female gender has not been studied in detail, despite multiple evidence suggesting a positive association. This review is directed at investigating the association between CMY and CRC in the female gender and aims at finding a potential cause for this association.CRC involves cancer of the sigmoid and rectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…34 In a more recent study of the female western population, a strong association was found between colorectal cancer and cholecystectomy. 35 These findings further implicate bile acids in the etiology of colon cancer.…”
Section: Human Prospective and Retrospective Studies Associate Bile A...mentioning
confidence: 85%
“…34 In a more recent study of the female western population, a strong association was found between colorectal cancer and cholecystectomy. 35 These findings further implicate bile acids in the etiology of colon cancer.…”
Section: Human Prospective and Retrospective Studies Associate Bile A...mentioning
confidence: 85%
“…Cholecystectomy can disturb bile flow and bile acid circulation, thus dysregulating gut microbiota (2). Growing evidence has linked these changes after cholecystectomy to the development of colorectal cancer (CRC) (3,4). Jiang et al discussed how cholecystectomy results in altered bile acid homeostasis and gut microbiota.…”
Section: Summary Of the Reviewsmentioning
confidence: 99%
“…ulcerative colitis). It most often occurs in the population as a sporadic disease, the occurrence of which is affected by older age, obesity, alcohol and cigarette consumption, excessive use of red meat and meat products, long-term use of androgens, diabetes and even cholecystectomy 3,4 .…”
Section: Introductionmentioning
confidence: 99%